Characterising the response of the mixed and the transitional layers to the passage of storms in the Sub-Antarctic Zone - Mpalweni, Ayanda (Department of Oceanography, 2020)
Mid-latitude storms are common in the Southern Ocean (SO) and have been shown to drive substantial vertical mixing, leaving behind wakes of perturbed upper ocean. The vertical extent and duration of the impact of these storms on the upper ocean remains unknown in this region, partly due to lack of observations in this remote part of the world. The mixed-layer depth (MLD) is used widely as proxy for vertical extent of upper-ocean mixing, with the assumption that it integrates the variability of atmospheric forcing. Recent studies have shown that this shear-driven mixing associated with storms can actually extend below the base of the MLD into the transitional layer (TL). Knowledge about the TL would help improve the mixing models of the upper ocean because it acts as a window/mediator between the deep ocean and the surface mixed layer (ML). However, the responses of the MLD and the transitional layer depth (TLD) have been shown to vary substantially between different storm events at similar locations. In this study, these two diagnostics, the MLD and TLD, have been used to investigate the response of the upper ocean mixing to storms in the Sub-Antarctic Zone (SAZ) and to further interrogate the relevance of the MLD as a proxy for mixing extent at these short temporal scales. This is explored during the summer period when the storm-driven mixing is thought to maintain primary production via enhanced nutrient supply. I used data collected from high-resolution autonomous gliders in pseudo-mooring mode, which remotely sampled the SAZ from spring to summer documenting the passage of storm events. Four storms of different magnitude were analysed in summer, and two different modes of the upper ocean response were identified. In the first mode, the MLD deepened during a storm, with little or no changes in the vertical structure of temperature and salinity in the layer below. The second mode was characterized by changes in the TL properties, which deepened at times; the MLD however did not respond to this storm forcing. In the pair of storms that was more in line with the classical response (i.e first mode), the vertical stratification in the upper ocean structure was eroded during the storm and after the storm. In the other case (i.e the 5second mode), however, the vertical stratification was enhanced during the passage of the storm and after the storm. These contrasting responses from both these storms can be linked to a number of atmospheric and oceanic factors; the atmospheric factor was the wind forcing extent (magnitude and duration). The oceanic factor that might have played a role is the pre-existing vertical stratification (depth and strength) within the water column. These two factors conspired to bring about upper ocean changes associated with the passing of storms. It has been shown here that most of the changes are indeed occurring in the transitional layer below the MLD. The MLD, which is used widely by the oceanographic community as a proxy for the integrated effect of surface mixing on many temporal scales, does not always capture the full response of upper-ocean mixing driven by the transient synoptic events.